IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN PNS PADA BADAN PEMBERDYAAN MASYARAKAT DAN PEMERINTAHAN DESA DAERAH PROVINSI SULAWESI TENGAH - Warna, Warna (Katalogis, 2017)
This study was to analyze the implementation of additional income policy at Central Sulawesi Board for Village Governance and Community Empowerment, why the implementation had not been effective and what the inhibiting factors. Research methods: qualitative research with descriptive method, informants amounted to 5 people and were selected based on purposive sampling. Data collection techniques: interview, observation, and documentation. The results of the study showed that the implementation of the additional income policy had not been run well, for three of the four dimensions that were examined had not run well, namely: first, communication especially socialization aspect had not been maximized, second, quantity of human resources was not adequate, as well as funding, facilities, and infrastructures had less supports for the implementation of the policy. Third, dispositions and attitudes including honesty, democrative nature, and commitment had been run by the implementors, but not maximized so that the implementation was not yet effective. While however, the bureaucratic structure, namely duties and functions, had been clear so there is no fragmentation and flexibility. The inhibiting factors were limited funding, resources, facilities, and infrastructures in the implementation.